2000
DOI: 10.1143/jpsj.69.259
|View full text |Cite|
|
Sign up to set email alerts
|

Ground State Phase Diagram of Frustrated S = 1 XXZ chains: Chiral Ordered Phases

Abstract: The ground-state phase diagram of frustrated S = 1 XXZ spin chains with the competing nearest-and next-nearest-neighbor antiferromagnetic couplings is studied using the infinitesystem density-matrix renormalization-group method. We find six different phases, namely, the Haldane, gapped chiral, gapless chiral, double Haldane, Néel, and double Néel (uudd) phases. The gapped and gapless chiral phases are characterized by the spontaneous breaking of parity, in which the long-range order parameter is a chirality… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 34 publications
5
106
1
Order By: Relevance
“…However, we point out that the full 1/r α long-range interactions, frustrated or not, will result in power-law decaying correlation functions in the gapped phases (see Ref. 57 for details); such correlations are absent in models with next-nearest-neighbor interactions [76][77][78][79] . For J xy = −1, where long-range interactions in the x − y plane are not frustrated, the phase diagram [ Fig.…”
Section: Model Hamiltonian and Phase Diagramsmentioning
confidence: 92%
“…However, we point out that the full 1/r α long-range interactions, frustrated or not, will result in power-law decaying correlation functions in the gapped phases (see Ref. 57 for details); such correlations are absent in models with next-nearest-neighbor interactions [76][77][78][79] . For J xy = −1, where long-range interactions in the x − y plane are not frustrated, the phase diagram [ Fig.…”
Section: Model Hamiltonian and Phase Diagramsmentioning
confidence: 92%
“…In a zigzag spin chain system with spin S = 1, the ground state phase diagram ͑at temperature T =0͒ as a function of XXZ anisotropy and ratio between nearest-neighbor ͑NN͒ and next-nearest-neighbor ͑NNN͒ interactions exhibits six different phases. 2,3 In addition to two Néel ordered phases and two phases with a Haldane gap, there exists a large phase region called a gapless chiral phase where the chirality exhibits long-range order without accompanying spin order, and a small phase region where there is a gapped chiral phase.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations have shown that for a one-dimensional spin S = 1 chain with antiferromagnetic nearest-neighbor interaction J 1 and frustrating nextnearest-neighbor antiferromagnetic interaction J 2 , the magnetic ground state shows gapped or gapless chiral ordering depending on the the anisotropy of the spin chain being XY or XXZ and on the ratio J 2 /J 1 . [37][38][39] The system does not show any long-range ordering of the spins.…”
Section: High Pressure Powder X-ray Diffraction On LIV 2 O 4 Crystalsmentioning
confidence: 93%
“…However, numerical calculations have shown that the influence of frustrating next-nearest-neighbor (NNN, J 2 ) interactions play a significant role and depending on the J 2 /J 1 ratio, can lead to incommensurate helical spin structures which may be gapped or gapless. [37,38,[146][147][148]] Such a system is described by the XXZ Hamiltonian…”
Section: A1 Introductionmentioning
confidence: 99%